Stellar yields for chemical evolution modelling. Issue Volume 9:Issue S298(2013) (6th January 2014) - Karakas, Amanda I.
Abstract: Stellar yields are a key ingredient in chemical evolution models. Stars with masses as low as 0.9M⊙, which have an age less than that of our Galaxy at low metallicity, can contribute to the chemical evolution of elements. Stars less than about 8–10M⊙ experience recurrent mixing events that can significantly change the surface composition of the envelope. Evolved stars are observed with surface enrichment in carbon, nitrogen, fluorine, and heavy elements synthesized by the slow neutron capture process (the s -process). These stars release their nucleosynthesis products through stellar outflows or winds, in contrast to massive stars that explode as core-collapse supernovae. Here I review stellar yields for stars up to 10M⊙, including a brief discussion of their uncertainties and shortcomings. Finally, I discuss efforts by various groups to address these issues and to provide homogeneous yields for low and intermediate-mass stars covering a broad range of metallicities.